2016
DOI: 10.1016/j.rpped.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoterapia em pacientes com fibrose cística na fase de pré‐diabetes: uma revisão sistemática

Abstract: There are theoretical reasons to believe that insulin has a beneficial effect in the studied population. The different methods and populations assessed in the studies do not allow us to state whether early insulin therapy should or should not be carried out in patients with cystic fibrosis prior to the diagnosis of diabetes. Therefore, studies with larger samples and insulin use standardization are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…O DRFC é a comorbidade mais comum e com elevada morbimortalidade em pacientes com FC (PU, 2016). Embora a DRFC ocorra, predominantemente, em indivíduos adultos com FC, a doença endócrino-metabólica pode apresentar sinais precoces durante a infância e adolescência, como declínio da velocidade e declínio do ganho de peso (DELLA MANNA, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O DRFC é a comorbidade mais comum e com elevada morbimortalidade em pacientes com FC (PU, 2016). Embora a DRFC ocorra, predominantemente, em indivíduos adultos com FC, a doença endócrino-metabólica pode apresentar sinais precoces durante a infância e adolescência, como declínio da velocidade e declínio do ganho de peso (DELLA MANNA, 2008).…”
Section: Discussionunclassified
“…O esquema do uso de insulina, que necessita ser instituído precocemente após diagnóstico de DRFC, deve ser titulado e avaliado individualmente para cada paciente. O tratamento precoce e adequado proporciona maior sobrevida e melhor condição clínica, incluindo estabilização da função pulmonar e benefício do status nutricional devido à reversão do catabolismo proteico (PU, 2016).…”
Section: Discussionunclassified
“…Recent guidelines recommend annual routine OGTT screening for people above the age of 10. Even though OGTT serves as a basis for defining CFRD, its thresholds were established in diabetes without CF, and were not designed to detect hyperglycaemiaassociated risk of deterioration in lung function or under-nutrition [39,45]. Considering the practical challenges of OGTT and the low frequency of screening, according to the 2018 report of the Cystic Fibrosis Foundation patient registry (approximately 61.3% of children, aged between 10 and 17, and 33.8% of adults), the need for a more convenient screening method is urgent [3].…”
Section: Ogttmentioning
confidence: 99%
“…In CF, the deleterious clinical effects associated with CFRD often manifest themselves before dysglycaemia reaches conventional thresholds for diabetes and hence earlier intervention has been advocated by some guidelines, particularly where early dysglycaemia is seen concurrently with nutritional and/or pulmonary decline 47. A handful of small studies have explored this strategy and although positive results were reported by some, a systematic review found the overall evidence base remains poor 48. Large prospective studies are underway and will provide more evidence in the coming years (“CF-IDEA Trial” clinicaltrials.gov: CT01100892 and “The Impact of Insulin Therapy on Protein Turnover in Pre-Diabetic Cystic Fibrosis Patients” clinicaltrials.gov: NCT02496780).…”
Section: Managementmentioning
confidence: 99%